Changes in setting time of alginate impression material with different water temperature - Decky J. Indrani; Niti Matram (Universitas Airlangga, 2013)
Background: Previous studies showed that setting process of alginates can be influenced by temperature. Purpose: To determine the changes in setting time due to differences in water temperature and to determine the correlation between water temperature and the setting time. Methods: Seven groups of dough alginate were prepared by mixing alginate powder and water, each using a temperature between 13° C-28° C with a interval of 2.5° C. A sample mold (Θ = 30 mm, t = 16 mm) was placed on a flat plate and filled with doug alginate. Immediately the flat end of a polished acrylic rod was placed in contact with the surface of dough alginate. Setting time of alginat was measured from the starting of the mix to the time when the alginate does not adhere to the end of the rod. Setting time alginate data were analyzed using one way ANOVA, LSD and Pearson. Results: Setting time of alginate with water temperature between 13° C-28° C were 87 to 119.4 seconds and were significantly different (p < 0.01). The setting time between group were also significantly different (p<0.01). There was an inverse correlation between water temperature and the setting time (r = -0.968).